Pembuatan Pengawet Alami Ikan Baronang (Siganus vermiculatus) dari Kayu Secang (Caesalpinia sappan L.) Menggunakan Ekstraksi Berbantu Gelombang Ultrasonik - Fitriani, Dea Syifa; Soimah, Siti; Kurniasari , Laeli (Talenta Publisher (Universitas Sumatera Utara), 2025)
This research aims to make a natural preservative of secang wood against baronang fish. The active flavonoid compounds of secang wood can function as antioxidants, antimicrobials, and antibacterials. Secang wood extract is obtained by ultrasonic extraction with a 60% ethanol solvent. Variable temperature and extraction ratio are the most optimal at 50 °C and a ratio (w/v) of 1:20. The extracts obtained were analysed for total phenolic levels, antioxidant levels, water content, and ash content. The extract is then used as a baronang fish preservative with a concentration of 600 ppm and 1200 ppm at room temperature and refrigerator. The result is a phenolic content of 2,24 mgGAE/g, a water content of 38,96%, an ash content of 0,65%, and an antioxidant content of 109,25 ppm. Preservation results were analysed total plate number at 3 hours, 6 hours, and 9 hours, as well as the average microbial growth at 9 hours of incubation. The result exceeds the quality standard of fresh fish SNI 2729:2013, which is 5,70 CFU/g. The longer the storage time of baronang fish, the more microbes grow, which is closely related to organoleptic analysis, which decreases its freshness rate.